LOCAL AND INTERNATIONAL FACTORS OF RETURNS IN FINANCIAL MARKETS:EVOLUTION OF INVESTMENT PREMIUMS VALUATION MODELS (Вісник: Міжнародні відносини, 2021)
The paper suggests retrospective analysis of investment premiums valuation models. Their place in contemporary theory of internationalportfolio investing is defined. Main phases of these models' evolution are revealed, uppermost considering incorporation of local and internationalfactors of expected returns. Basic features of these phases are discovered. Dominance of the CAPM model in the framework of expected returnsvaluation concept is validated. This model is underlying major part of the science in this field development, particularly zero beta model andintertemporal model. Gnoseological conditions of models including international factors of securities premiums origin and development are identified.Specific attention is paid to models considering currency risk factor – one of the key factors of expected returns in international investmentenvironment. Major events of the world economy that actualized the necessity of considering currency risks while valuing investment premiums aresingled out. International capital asset pricing model as one that incorporates currency risk factor during expected returns valuation in the best wayis examined. Comparative analysis of international CAPM and the approach of using the traditional model in international market is carried out.Although no evident advantage of any is fixed, existing empirics proves that the latter is much more convenient in terms of its usage, and is actuallyused much more often. The rationale of methodological priority of using the term "premium" rather than "expected return" is presented.Methodological indifference between the terms "price" and "expected return" in the current context is reported.
Keywords: portfolio paradigm of international investing, security investment premium, capital asset pricing model (CAPM), expected returns valuation concept, currency risk, international factors of investment premiums, risk-free return, intertemporal CAPM, zero-beta model, two-fund theorem, international CAPM.